2012
DOI: 10.1371/journal.pone.0050654
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 and TLR4 Mediate Differential Responses to Limb Ischemia through MyD88-Dependent and Independent Pathways

Abstract: IntroductionThe danger signal HMGB1 is released from ischemic myocytes, and mediates angiogenesis in the setting of hindlimb ischemia. HMGB1 is a ligand for innate immune receptors TLR2 and TLR4. While both TLR2 and TLR4 signal through myeloid differentiation factor 88 (MyD88), TLR4 also uniquely signals through TIR-domain-containing adapter-inducing interferon-β (TRIF). We hypothesize that TLR2 and TLR4 mediate ischemic myocyte regeneration and angiogenesis in a manner that is dependent on MyD88 signaling.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…In TLR2KO mice, we have shown that this recovery was not observed with persistence of necrotic myocytes and grossly abnormal vascular structures supporting the role of TLR2 in angiogenesis in vivo (9). This result was confirmed in TLR4KO mice, where perfusion and vascularity in the ischemic hindlimb were increased compared with WT mice.…”
Section: T L R 4 D E T E R S P E R F U S I O N R E C O V E R Ysupporting
confidence: 73%
See 3 more Smart Citations
“…In TLR2KO mice, we have shown that this recovery was not observed with persistence of necrotic myocytes and grossly abnormal vascular structures supporting the role of TLR2 in angiogenesis in vivo (9). This result was confirmed in TLR4KO mice, where perfusion and vascularity in the ischemic hindlimb were increased compared with WT mice.…”
Section: T L R 4 D E T E R S P E R F U S I O N R E C O V E R Ysupporting
confidence: 73%
“…*p < 0.03, TLR4KO to TLR2KO mice; 3-5 animals/group, ANOVA. (C) PMNs were identified on H and E sections by using characteristic nuclear morphology as described (9). Percent PMN nuclei relative to total nuclei is shown from tibialis anterior muscle obtained 3 d after FAL in control, TLR2/4 double KO, TLR2KO and TLR4KO mice (p value nonsignificant among the groups).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular HMGB1 interacts with cell surfaceexpressed receptors: RAGE, TLR2 and TLR4, which promote the activation of the MyD88-mediated NF-kB pathway. 7,[32][33][34] HMGB1 or HMGB2 released from necrotic cells can exert a proinflammatory effect by transmitting a damage signal to neighboring cells. 35,36 In the cytoplasm, HMGBs bind immunogenic nucleotides and deliver them to the cytosolic nucleic acid sensors retinoic acid-inducible gene I, MDA5, AIM2 and DAI and to the endosome nucleic acid-sensing TLRs (TLR3, TLR7 and TLR9).…”
Section: Discussionmentioning
confidence: 99%